A corrosion and solvent resistant coating material for food packaging and a method of making the same
Patent Information
- Application Number
- CN202610143172.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-02
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-02-02
AI Technical Summary
[0005]如中国专利CN121379296A,提供了一种用于食品包装的环氧改性涂料,其以改性环氧树脂为主要原料,大幅改善了在涂布时涂层的单涂效果,减少橘皮和流平不良现象,达到环氧涂料的双涂效果,然而以环氧类涂料作为食品包装涂层材料,将面临化学物质迁移风险,安全性有待进一步验证,且在一些高温溶剂环境下容易出现附着力下降以及迁移加快现象,存在微缺陷风险
1、本发明申请提供的食品包装用涂层材料,作为一种综合性能优异的食品包装用单层涂层,其在高温高湿、接触油脂及酸性内容物等复杂苛刻环境下,仍能保持优异的防腐、阻隔与耐溶剂性,有效抵御溶剂渗透与溶胀,同时具备优异的基材附着力与储存稳定性,确保了其安全应用,且工艺适应性强,适于规模化生产。
Abstract
Description
Technical Field
[0001] This invention relates to the field of food packaging, and in particular to an anti-corrosion and solvent-resistant coating material for food packaging and its preparation method. Background Technology
[0002] The performance of food packaging materials is crucial for ensuring food safety and extending shelf life. Coating technology, by forming a functional film on the substrate surface, can effectively block the penetration of oxygen, water vapor, oils, and external chemical solvents, while inhibiting microbial growth, and has become an important means of improving the overall performance of packaging.
[0003] Currently, most widely used packaging coating materials are based on synthetic polymers, such as polyethylene, polyvinylidene chloride, and polyesters. These materials provide basic barrier properties through their dense molecular structure and often incorporate antimicrobial components through blending or surface modification to impart preservative functions. In terms of processing, uniform coating preparation and adhesion are mainly achieved through methods such as extrusion lamination, solvent-based coating, or vacuum deposition. These technologies can, to a certain extent, meet the needs of conventional food packaging.
[0004] However, with the diversification of food types and the increasing complexity of storage environments, the limitations of existing coating materials are becoming increasingly apparent. For example, the barrier properties of most polymer coatings significantly degrade under high humidity or high temperature conditions, leading to increased permeability to water vapor and oxygen, which affects the preservation of hygroscopic or easily oxidized foods. Regarding solvent resistance, existing coatings are insufficiently resistant to food contents rich in oils, alcohols, or acidic components; long-term contact may cause the coating to swell, migrate, or even decompose, affecting not only packaging integrity but also potentially posing food safety hazards. Furthermore, inorganic nanoparticles or small molecule additives added to improve preservation or barrier properties pose a risk of migration into food and are subject to increasingly stringent safety regulations. From an environmental and sustainability perspective, some halogen-containing or recalcitrant coating materials also face elimination pressure.
[0005] For example, Chinese patent CN121379296A provides an epoxy-modified coating for food packaging. It uses modified epoxy resin as the main raw material, which greatly improves the single-coat effect of the coating during application, reduces orange peel and poor leveling, and achieves the double-coat effect of epoxy coatings. However, using epoxy coatings as food packaging coating materials will face the risk of chemical migration, and the safety needs to be further verified. In addition, in some high-temperature solvent environments, the adhesion is prone to decrease and the migration is accelerated, which poses a risk of micro-defects. Summary of the Invention
[0006] The purpose of this invention application is to provide a food packaging coating material that can remain stable under complex usage environments, has excellent corrosion resistance, solvent resistance and certain barrier properties, and is easy to prepare, safe and suitable for large-scale production.
[0007] To achieve the above objectives, the present invention provides the following technical solution: The first aspect of this invention provides a corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 90-120 parts of main film-forming resin, 2-4 parts of crosslinking curing agent, 4-8 parts of composite reinforcing agent, 3-6 parts of barrier filler, 0.5-1.2 parts of adhesion promoter, 1-1.5 parts of lubricant, 0.1-0.2 parts of defoamer, 0.2-1 parts of pH adjuster, and 10-20 parts of deionized water.
[0008] In a preferred embodiment, the main film-forming resin is an aqueous acrylic resin emulsion.
[0009] In a preferred embodiment, the average particle size of the aqueous acrylic resin emulsion is 35~100nm.
[0010] In a more preferred embodiment, the average particle size of the aqueous acrylic resin emulsion is 35~50nm.
[0011] In a preferred embodiment, the aqueous acrylic resin emulsion is specifically Joncryl 95, manufactured by BASF, Germany.
[0012] In a preferred embodiment, the mass ratio of the main film-forming resin, the crosslinking curing agent, and the composite reinforcing agent is (9.5~11):(0.25~0.35):(0.4~0.6).
[0013] In a preferred embodiment, the mass ratio of the main film-forming resin, the crosslinking curing agent, and the composite reinforcing agent is (10~10.5):(0.3~0.35):(0.45~0.55).
[0014] In a preferred embodiment, the crosslinking curing agent is a combination of polycarbodiimide and aziridine crosslinking agent.
[0015] In a preferred embodiment, the mass ratio of the polycarbodiimide to the aziridine crosslinking agent is (3~5):(2~3).
[0016] A more preferred embodiment is that the mass ratio of the polycarbodiimide to the aziridine crosslinking agent is (3.5~4.2):(2~2.4).
[0017] In a preferred embodiment, the aziridine crosslinking agent is specifically CX-100, manufactured by Hubei Langbowan Biotechnology.
[0018] The compound crosslinking scheme used in this invention application effectively improves the overall performance and stability of the coating material. Polycarbodiimide, as the main crosslinking agent, reacts with the resin carboxyl groups to form highly hydrolysis-resistant chemical bonds, providing a foundation for long-term solvent resistance and durability of the coating. Simultaneously, additional crosslinking agents react with various functional groups to rapidly establish a network framework in the early stages of curing, effectively improving crosslinking efficiency and initial coating performance. The combined effect of these two methods ensures the sufficiency and uniformity of the crosslinking reaction, avoiding reaction dead zones, and significantly enhancing the coating's resistance to penetration and swelling in complex food contact environments such as humid heat, oiliness, and acidity. This results in a comprehensive improvement in barrier properties, corrosion resistance, and physical and mechanical properties.
[0019] In a preferred embodiment, the composite reinforcing agent is a combination of polycaprolactone diol, epoxidized soybean oil, and propyl gallate.
[0020] In a preferred embodiment, the mass ratio of polycaprolactone diol, epoxidized soybean oil and propyl gallate is (4.5~6):(2.5~4):(1~2).
[0021] A more preferred embodiment is that the mass ratio of polycaprolactone diol, epoxidized soybean oil and propyl gallate is (5~5.5):(3.5~4):(1.6~2).
[0022] In a preferred embodiment, the number-average molecular weight of the polycaprolactone diol is 1000~3000 Da.
[0023] In a preferred embodiment, the number-average molecular weight of the polycaprolactone diol is 2000~3000 Da.
[0024] Further addition of composite reinforcing agents optimizes the performance of the coating material. Flexible long-chain segments are effectively embedded and toughened into the cross-linked network, giving the coating excellent flexibility and low-temperature impact resistance. The long-chain structure provides lasting flexibility and participates in cross-linking, enhancing the uniformity and density of the network. Furthermore, through dense hydrogen bond interactions with polymer chains, the cohesion and rigidity of the network are significantly strengthened. Under these combined effects, the mechanical properties of the coating, such as flexural strength and impact resistance, are greatly improved. Moreover, by forming a denser and stronger network, the coating's ability to resist solvent penetration and swelling is fundamentally enhanced, and the anti-corrosion effect is indirectly extended by maintaining the integrity of the barrier.
[0025] In a preferred embodiment, the barrier filler is at least one of silane-modified kaolin, synthetic mica, stearic acid-modified talc, and precipitated barium sulfate.
[0026] In a more preferred embodiment, the barrier filler is silane-modified kaolin or stearic acid-modified talc.
[0027] A more preferred embodiment is that the barrier filler is stearic acid-modified talc.
[0028] In a preferred embodiment, the average mesh size of the barrier filler is 600-1250 mesh.
[0029] In a more preferred embodiment, the average mesh size of the barrier filler is 1000-1250 mesh.
[0030] In a preferred embodiment, the adhesion promoter is at least one selected from γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.
[0031] A more preferred embodiment is that the adhesion promoter is γ-aminopropyltriethoxysilane or N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0032] In a more preferred embodiment, the adhesion promoter is γ-aminopropyltriethoxysilane.
[0033] In a preferred embodiment, the lubricant is at least one selected from polyethylene wax, oxidized polyethylene wax, ethylene bis-stearamide, and polypropylene wax.
[0034] A more preferred embodiment is that the lubricant is oxidized polyethylene wax.
[0035] In a preferred embodiment, the pH adjuster is at least one selected from 2-amino-2-methyl-1-propanol, ammonia, and triethanolamine.
[0036] In a more preferred embodiment, the pH adjuster is 2-amino-2-methyl-1-propanol or ammonia.
[0037] In a more preferred embodiment, the pH adjuster is 2-amino-2-methyl-1-propanol.
[0038] The second aspect of this invention provides a method for preparing the above-mentioned anti-corrosion and solvent-resistant coating material for food packaging, specifically including the following steps: S1: Barrier filler, adhesion promoter, and a portion of deionized water are added and sheared and dispersed at 600-800 rpm for 20-25 min to obtain a preliminary slurry. The composite reinforcing agent raw material is added to the remaining deionized water, and the mixture is slowly heated to 65-75°C and stirred at a low speed of 80-100 rpm until a uniform primary emulsion is formed; S2: The main film-forming resin is added to a reaction vessel and stirred at 200-300 rpm for 3-5 min. The preliminary slurry and primary emulsion are then added sequentially, with each addition being uniform. Stir at 300-400 rpm for 10-15 min, add the remaining raw materials and adjust the pH to 8-8.5, stir at 120-200 rpm for 10-15 min, filter to obtain the coating, and cure at 25-28℃ for 12-16 h; S3: Using corona-treated BOPP with ≥50 dyn / cm as the base, apply the coating to ensure a dry film thickness of 1.8-2.3 μm, pre-dry at 85-90℃ for 2-4 min, then heat and cure at 130-135℃ for 12-20 min until fully cured, and then cure at 25-30℃ for 40-48 h to obtain the final product.
[0039] Compared with the prior art, the advantages and beneficial effects of this invention application are as follows: 1. The coating material for food packaging provided in this application is a single-layer coating for food packaging with excellent comprehensive performance. It can still maintain excellent anti-corrosion, barrier and solvent resistance in complex and harsh environments such as high temperature and humidity, contact with oil and acidic contents, effectively resist solvent penetration and swelling, and at the same time have excellent substrate adhesion and storage stability, ensuring its safe application. It also has strong process adaptability and is suitable for large-scale production.
[0040] 2. The compound crosslinking scheme adopted in this invention application effectively improves the overall performance and performance stability of the coating material. By rapidly establishing a network skeleton in the early stage of curing, it effectively improves the crosslinking efficiency and the initial performance of the coating. The combined effect of the two ensures the sufficiency and uniformity of the crosslinking reaction, avoids reaction dead zones, and significantly enhances the coating's resistance to penetration and swelling in complex food contact environments such as humid heat, oiliness, and acidity. Thus, it achieves a comprehensive improvement in barrier properties, corrosion resistance, and physical and mechanical properties.
[0041] 3. This invention further incorporates a composite reinforcing agent to effectively embed flexible long-chain segments and toughen the crosslinking network, giving the coating excellent flexibility and low-temperature impact resistance. The long-chain structure provides lasting flexibility, while participating in crosslinking to enhance the uniformity and density of the network. Furthermore, through the formation of dense hydrogen bonds with the polymer chains, it significantly strengthens the cohesion and rigidity of the network, thereby greatly improving the overall performance of the coating material. Detailed Implementation
[0042] The technical solutions in the embodiments of this invention will be clearly and completely described below. The described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0043] In the following specific embodiments, unless otherwise specified, the sources / preparation methods of some raw materials are as follows: The water-based acrylic resin emulsion is specifically Joncryl 95, manufactured by BASF, Germany.
[0044] Polycarbodiimide, premium grade, Hubei Langbowan Biotechnology.
[0045] The propidium crosslinking agent is specifically CX-100, manufactured by Hubei Langbowan Biotechnology.
[0046] Polycaprolactone diol PCL2000, Jining Fangyu Chemical Co., Ltd.
[0047] Epoxidized soybean oil, food grade, Shandong Senya New Materials.
[0048] Stearic acid modified talc powder, 1250 mesh, Shijiazhuang Yitian Mineral Products.
[0049] Defoamer TEGO-8030, Greenlink (Jining) Chemical.
[0050] Example 1 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 100 parts of main film-forming resin, 3.2 parts of crosslinking curing agent, 4.8 parts of composite reinforcing agent, 4.5 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 12 parts of deionized water.
[0051] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0052] The crosslinking curing agent is a combination of polycarbodiimide and aziridine crosslinking agent CX-100, with a mass ratio of 3.8:2.2.
[0053] The composite reinforcing agent is a combination of polycaprolactone diol PCL2000, epoxidized soybean oil and propyl gallate, with a mass ratio of 5.3:4:1.7.
[0054] The barrier filler is stearic acid modified talc powder with an average mesh size of 1250 mesh.
[0055] The adhesion promoter is γ-aminopropyltriethoxysilane; the lubricant is oxidized polyethylene wax; the defoamer is TEGO-8030; and the pH adjuster is 2-amino-2-methyl-1-propanol.
[0056] A method for preparing a corrosion-resistant and solvent-resistant coating material for food packaging includes the following steps: S1: Barrier filler, adhesion promoter, and a portion of deionized water are added and sheared and dispersed at 600 rpm for 25 min to obtain a preliminary slurry. The composite reinforcing agent raw material is added to the remaining deionized water, and the mixture is slowly heated to 70°C and stirred at 100 rpm until a uniform primary emulsion is formed. S2: The main film-forming resin is added to a reaction vessel and stirred at 250 rpm for 4 min. The preliminary slurry and primary emulsion are added sequentially, and each addition is stirred at 400 rpm for 12 min. After adding the remaining raw materials and adjusting the pH to 8.2, the mixture is stirred at 180 rpm for 15 min. The resulting coating is filtered and cured at 25°C for 14 h. S3: Using corona-treated BOPP with a density ≥50 dyn / cm as a substrate, the coating is applied to ensure a dry film thickness of 2 μm. The coating is pre-dried at 90°C for 4 min, then cured at 130°C for 18 min until fully cured. After curing, the coating is cured at 28°C for 48 h to obtain the final product.
[0057] Example 2 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 95 parts of main film-forming resin, 2.8 parts of crosslinking curing agent, 4.4 parts of composite reinforcing agent, 4.2 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 10 parts of deionized water.
[0058] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0059] The crosslinking curing agent is a combination of polycarbodiimide and aziridine crosslinking agent CX-100, with a mass ratio of 3.8:2.2.
[0060] The composite reinforcing agent is a combination of polycaprolactone diol PCL2000, epoxidized soybean oil and propyl gallate, with a mass ratio of 5.7:3.8:1.5.
[0061] The barrier filler is stearic acid modified talc powder with an average mesh size of 1250 mesh.
[0062] The adhesion promoter is γ-aminopropyltriethoxysilane; the lubricant is oxidized polyethylene wax; the defoamer is TEGO-8030; and the pH adjuster is 2-amino-2-methyl-1-propanol.
[0063] A method for preparing a corrosion-resistant and solvent-resistant coating material for food packaging includes the following steps: S1: Barrier filler, adhesion promoter, and a portion of deionized water are added and sheared and dispersed at 600 rpm for 25 min to obtain a preliminary slurry. The composite reinforcing agent raw material is added to the remaining deionized water, and the mixture is slowly heated to 70°C and stirred at 100 rpm until a uniform primary emulsion is formed. S2: The main film-forming resin is added to a reaction vessel and stirred at 250 rpm for 4 min. The preliminary slurry and primary emulsion are added sequentially, and each addition is stirred at 400 rpm for 12 min. After adding the remaining raw materials and adjusting the pH to 8.2, the mixture is stirred at 180 rpm for 15 min. The resulting coating is filtered and cured at 25°C for 14 h. S3: Using corona-treated BOPP with a density ≥50 dyn / cm as a substrate, the coating is applied to ensure a dry film thickness of 2 μm. The coating is pre-dried at 90°C for 4 min, then cured at 130°C for 18 min until fully cured. After curing, the coating is cured at 28°C for 48 h to obtain the final product.
[0064] Example 3 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 110 parts of main film-forming resin, 3.4 parts of crosslinking curing agent, 5 parts of composite reinforcing agent, 4.8 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 14 parts of deionized water.
[0065] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0066] The crosslinking curing agent is a combination of polycarbodiimide and aziridine crosslinking agent CX-100, with a mass ratio of 4.5:2.
[0067] The composite reinforcing agent is a combination of polycaprolactone diol PCL2000, epoxidized soybean oil and propyl gallate in a mass ratio of 5:4:2.
[0068] The barrier filler is stearic acid modified talc powder with an average mesh size of 1250 mesh.
[0069] The adhesion promoter is γ-aminopropyltriethoxysilane; the lubricant is oxidized polyethylene wax; the defoamer is TEGO-8030; and the pH adjuster is 2-amino-2-methyl-1-propanol.
[0070] A method for preparing a corrosion-resistant and solvent-resistant coating material for food packaging includes the following steps: S1: Barrier filler, adhesion promoter, and a portion of deionized water are added and sheared and dispersed at 600 rpm for 25 min to obtain a preliminary slurry. The composite reinforcing agent raw material is added to the remaining deionized water, and the mixture is slowly heated to 70°C and stirred at 100 rpm until a uniform primary emulsion is formed. S2: The main film-forming resin is added to a reaction vessel and stirred at 250 rpm for 4 min. The preliminary slurry and primary emulsion are added sequentially, and each addition is stirred at 400 rpm for 12 min. After adding the remaining raw materials and adjusting the pH to 8.2, the mixture is stirred at 180 rpm for 15 min. The resulting coating is filtered and cured at 25°C for 14 h. S3: Using corona-treated BOPP with a density ≥50 dyn / cm as a substrate, the coating is applied to ensure a dry film thickness of 2 μm. The coating is pre-dried at 90°C for 4 min, then cured at 130°C for 18 min until fully cured. After curing, the coating is cured at 28°C for 48 h to obtain the final product.
[0071] Comparative Example 1 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 115 parts of main film-forming resin, 3.2 parts of crosslinking curing agent, 1.5 parts of composite reinforcing agent, 4.5 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 12 parts of deionized water.
[0072] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0073] The remaining implementation methods are the same as in Example 1.
[0074] Comparative Example 2 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 90 parts of main film-forming resin, 2.8 parts of crosslinking curing agent, 10.5 parts of composite reinforcing agent, 4.1 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 12 parts of deionized water.
[0075] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0076] The remaining implementation methods are the same as in Example 1.
[0077] Comparative Example 3 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 100 parts of main film-forming resin, 3.2 parts of crosslinking curing agent, 4.8 parts of composite reinforcing agent, 4.5 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 12 parts of deionized water.
[0078] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0079] The crosslinking curing agent is a combination of polycarbodiimide and aziridine crosslinking agent CX-100, with a mass ratio of 5:1.
[0080] The remaining implementation methods are the same as in Example 1.
[0081] Comparative Example 4 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 100 parts of main film-forming resin, 3.2 parts of crosslinking curing agent, 4.8 parts of composite reinforcing agent, 4.5 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 12 parts of deionized water.
[0082] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0083] The crosslinking curing agent is a combination of polycarbodiimide and aziridine crosslinking agent CX-100, with a mass ratio of 2.5:3.5.
[0084] The remaining implementation methods are the same as in Example 1.
[0085] Comparative Example 5 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 100 parts of main film-forming resin, 3.2 parts of crosslinking curing agent, 4.8 parts of composite reinforcing agent, 4.5 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 12 parts of deionized water.
[0086] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0087] The composite reinforcing agent is a combination of polycaprolactone diol PCL2000, epoxidized soybean oil and propyl gallate, with a mass ratio of 6:4.5:0.5.
[0088] The remaining implementation methods are the same as in Example 1.
[0089] Comparative Example 6 A corrosion-resistant and solvent-resistant coating material for food packaging, comprising, by weight, the following raw materials: 100 parts of main film-forming resin, 3.2 parts of crosslinking curing agent, 4.8 parts of composite reinforcing agent, 4.5 parts of barrier filler, 0.9 parts of adhesion promoter, 1.2 parts of lubricant, 0.2 parts of defoamer, 0.8 parts of pH adjuster, and 12 parts of deionized water.
[0090] The main film-forming resin is an aqueous acrylic resin emulsion, Joncryl 95, with an average particle size of 40 nm.
[0091] The composite reinforcing agent is a combination of polycaprolactone diol PCL2000, epoxidized soybean oil and propyl gallate, with a mass ratio of 7:2:2.
[0092] The remaining implementation methods are the same as in Example 1.
[0093] Performance testing 1. Total migration: The total migration of the prepared coating sample was tested with 10% ethanol at 40°C for 10 days. The test solution was evaporated, dried and the residue was weighed. The migration per unit area was calculated and the results were recorded in Table 1.
[0094] 2. Adhesion: The prepared coated sample was laminated with another uncoated BOPP substrate using Henkel Liofol UK 3640 adhesive. The lamination process must ensure that the cohesive force formed between the coating and the uncoated substrate is greater than the adhesion between the coating and its own substrate. The laminated sample was then fully cured for 72 hours. The cured composite film was cut into strips 25 mm wide and 200 mm long. The two substrates of the strips were peeled at a 90° angle, and a peel test was performed at a constant speed of 250 mm / min. The average value of the data during the peel stability phase, i.e., the first 25 mm and the last 25 mm, was recorded in Table 1.
[0095] 3. Solvent Resistance: The coating samples prepared in the examples and comparative examples were completely immersed in olive oil and 50 vt% ethanol aqueous solution, respectively, for testing. During the test, the containers were sealed and placed in a constant temperature environment of 23±2℃ for 60 days. After the period, the samples were taken out, and the surface was gently blotted dry with filter paper. The coating was observed to see if whitening, blistering, wrinkling, peeling, or dissolution occurred. If any phenomenon occurred, it was recorded as unqualified, otherwise it was recorded as qualified. 100 parallel tests were performed for each group of tests, and the pass rate results were recorded. The pass rates of olive oil and 50 vt% ethanol aqueous solution were tested separately and the results were recorded in Table 1.
[0096] 4. Temperature stability: The prepared coating sample was placed in a constant temperature oven and kept at 80±2℃ for 200h. After the oven, the sample was taken out and equilibrated at 23±2℃ and 50±5% RH for 24h. The coating sample after high temperature aging was tested according to the adhesion test scheme and compared with the initial data before aging to obtain the performance retention rate. The average value of 10 tests was recorded in Table 1.
[0097] Table 1 Performance Test Results Example 1 0.32 2.64 100 100 97.41 Example 2 0.41 2.66 100 100 96.96 Example 3 0.35 2.57 100 100 96.23 Comparative Example 1 0.57 2.24 94 97 89.36 Comparative Example 2 0.49 2.31 98 95 90.98 Comparative Example 3 0.53 2.43 96 96 92.34 Comparative Example 4 0.62 2.39 98 99 93.67 Comparative Example 5 0.44 2.41 97 94 94.17 Comparative Example 6 0.38 2.35 96 93 94.45 5. Specific migration: The coating samples prepared in Examples 1 to 3 were subjected to specific migration tests at 10% ethanol and 60°C for 10 days. The aziridine derivative and propyl gallate were quantitatively analyzed by LC-MS / MS and HPLC, respectively, and the results are recorded in Table 2.
[0098] Table 2 Specific migration results Example 1 Not detected (detection limit: 0.3 mg / L) Not detected (limit of quantitation: 3 mg / L) Example 2 Not detected (detection limit: 0.3 mg / L) Not detected (limit of quantitation: 3 mg / L) Example 3 Not detected (detection limit: 0.3 mg / L) Not detected (limit of quantitation: 3 mg / L) As shown in Tables 1 and 2, the test results of Examples 1-3 of this application demonstrate superior overall performance compared to Comparative Examples 1-6. The crosslinking and reinforcing agent schemes specified in this application, employed in Examples 1-3, effectively improve crosslinking efficiency and initial coating performance by rapidly establishing a network skeleton during the early stages of curing. The combined effect of these two agents ensures the sufficiency and uniformity of the crosslinking reaction, avoiding dead zones and significantly enhancing the coating's resistance to penetration and swelling in complex food contact environments such as humid heat, oiliness, and acidity. Furthermore, it enhances the uniformity and density of the network and, through dense hydrogen bond interactions with polymer chains, significantly strengthens the network's cohesion and rigidity, resulting in a substantial improvement in the overall performance of the coating material. In contrast, Comparative Examples 1-6, employing different technical solutions than those specified in this application, significantly reduced the effectiveness of their respective technical effects in the coating material system, ultimately leading to a marked weakening of their overall performance.
[0099] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A corrosion-resistant and solvent-resistant coating material for food packaging, characterized in that: By weight, the raw materials include: 90-120 parts of main film-forming resin, 2-4 parts of crosslinking curing agent, 4-8 parts of composite reinforcing agent, 3-6 parts of barrier filler, 0.5-1.2 parts of adhesion promoter, 1-1.5 parts of lubricant, 0.1-0.2 parts of defoamer, 0.2-1 parts of pH adjuster, and 10-20 parts of deionized water; The main film-forming resin is an aqueous acrylic resin emulsion with an average particle size of 35~100nm. The crosslinking curing agent is a combination of polycarbodiimide and aziridine crosslinking agent, with a mass ratio of (3.5~4.2):(2~2.4). The composite reinforcing agent is a combination of polycaprolactone diol, epoxidized soybean oil and propyl gallate, with a mass ratio of (5~5.5):(3.5~4):(1.6~2). The mass ratio of the main film-forming resin, crosslinking curing agent, and composite reinforcing agent is (9.5~11):(0.25~0.35):(0.4~0.6). The number-average molecular weight of the polycaprolactone diol is 1000~3000 Da.
2. The anti-corrosion and solvent-resistant coating material for food packaging according to claim 1, characterized in that: The barrier filler is at least one of silane-modified kaolin, synthetic mica, stearic acid-modified talc, and precipitated barium sulfate.
3. The anti-corrosion and solvent-resistant coating material for food packaging according to claim 2, characterized in that: The adhesion promoter is at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.
4. The anti-corrosion and solvent-resistant coating material for food packaging according to claim 3, characterized in that: The lubricant is at least one of polyethylene wax, oxidized polyethylene wax, ethylene bis-stearamide, and polypropylene wax.
5. The anti-corrosion and solvent-resistant coating material for food packaging according to claim 4, characterized in that: The average mesh size of the barrier filler is 600~1250 mesh.
6. The anti-corrosion and solvent-resistant coating material for food packaging according to claim 5, characterized in that: The pH adjuster is at least one of 2-amino-2-methyl-1-propanol, ammonia, and triethanolamine.
7. The anti-corrosion and solvent-resistant coating material for food packaging according to claim 6, characterized in that: The pH adjuster is 2-amino-2-methyl-1-propanol or ammonia.
8. A method for preparing a corrosion-resistant and solvent-resistant coating material for food packaging according to any one of claims 1 to 7, characterized in that: Specifically, the following steps are included: S1: Add the barrier filler, adhesion promoter, and a portion of deionized water, and shear and disperse at 600-800 rpm for 20-25 minutes to obtain the initial slurry. Add the composite reinforcing agent raw material to the remaining deionized water, slowly heat to 65-75℃, and stir at a low speed of 80-100 rpm until a uniform primary emulsion is formed. S2: Add the main film-forming resin to the reactor, stir at 200-300 rpm for 3-5 minutes, and then add the initial slurry and primary emulsion sequentially, stirring at 300-400 rpm for 10-15 minutes after each addition. After adding the remaining raw materials and adjusting the pH to 8-8.5, stir at 120-200 rpm for 10-15 min, filter to obtain the coating, and cure at 25-28℃ for 12-16 h; S3: Using BOPP with corona treatment ≥50 dyn / cm as the base, apply the coating to ensure a dry film thickness of 1.8-2.3 μm, pre-dry at 85-90℃ for 2-4 min, then keep warm at 130-135℃ for 12-20 min until fully cured, and then cure at 25-30℃ for 40-48 h to obtain the final product.
Citation Information
Patent Citations
Epoxy modified coating for food packaging as well as preparation method and application of epoxy modified coating
CN121379296A
Packaging coating containing water-dispersible acrylic block copolymer
CN112384581A
Completely biodegradable plastic bag and preparation method thereof
CN120648187A
Coating composition and PET (Polyethylene Terephthalate) coating film prepared from same
CN121086654A
